Microbiología periodontal: Pruebas diagnósticas, una revisión - Moromi Nakata, Hilda (2003)
In order to show a global vision of bacterial agents in periodontal disease, it is reviewed the etiologic factor of bacterial microorganisms in periodontal disease the related microorganisms and diagnostic techniques pointing out its advantages and limitations.